Natural Changbai mineral water reduces obesity risk through regulating metabolism and gut microbiome in a hyperuricemia male mouse model - Li, Maichao; Guo, Kai; He, Yuwei; Li, Hailong; Sun, Wenyan; Yuan, Xuan; Liu, Zhen; Li, Xinde; Merriman, Tony R.; Li, Changgui; Zhang, Hui (Frontiers in Nutrition, 2024)
Access to clean and safe drinking water is essential. This study aimed to evaluate the effect of a kind of small molecular natural mineral water, C-cell mineral water on hyperuricemia male mice metabolism condition. A 13-week drinking water intervention study was conducted in Uox-knockout mice (KO). The hepatic metabolite profiling and related genes expression were detected by UPLC-TOF-MS and transcriptomic, and the gut microbiota of KO mice was determined by metagenomics sequencing. Results showed that the body weight of mice fed with C-cell water was remarkably lower than that of control mice on D 77 and D 91. Hepatic metabolite profiling revealed a shift in the pathway of glycine, serine and threonine metabolism, pantothenate and CoA biosynthesis, and biosynthesis of cofactors in KO mice fed with C-cell mineral water. Increased energy metabolism levels were related to increased hepatic expression of genes responsible for coenzyme metabolism and lipid metabolism. Gut microbiota was characterized by increasing activity of beneficial bacteria Blautia, and reducing activity of pathobiont bacteria Parasutterella. These genera have been reported to be associated with obesity. Small molecular mineral-rich natural water ingestion regulates metabolism and gut microbiota, protecting against obesity induced by hyperuricemia through mediating a microbiota-liver axis.